PERKEMBANGAN MASYARAKAT DESA: STUDI PERUBAHAN SOSIAL MASYARAKAT GAMPONG JEUMPEUK KABUPATEN ACEH JAYA - Nurkhalis Nurkhalis; Zulfadhli Zulfadhli (Prodi Sosiologi FISIP Universitas Teuku Umar, 2017)
Social change is an event (phenomenon) that is common in society, over time social change, on the one side gives positive impact (cooperation or kinship) and the other side can also be negative (disputes, individual and even conflict). The problem formulations in this study are (1). What is the social change of society that happened before and after the tsunami in Gampong Jeumpheuk, Aceh Jaya. (2). What are the factors that cause social change of society in Gampong Jeumpheuk, Aceh Jaya. The method used in this research is qualitative-descriptive method, where the process of collecting data in the field using the technique of observation and in-depth interview, previously determined informant research. Determination of informant used Purposive Sampling Technique. The theoretical basis used by the theory of symbolic interactionism, is a way of looking at individuals and social and attempts to perceive that man is the creator of the actors, the execution, and the self-directed. The results show that the social changes of the gampong jeumpheuk community have faded (shifted) from before. It can be seen from comparing before and after tsunami and also proven from several factors that lead to economic factors, education, social and moral culture. Keywords: Society, Village, Social Change